Improvement of Municipal Waste Management by Applying the Smart City Concept (Proceedings of Faculty of Civil Engineering, 2023)
This paper provides an overview of the possibility of improving municipal waste management by applying the concept of a smart city, i.e., modern technologies that enable efficient organization of waste collection and charging for services by quantity. The described improvements would be particularly important for larger urban centers or smaller towns in coastal areas due to problems arising from the waste management system burden during the tourist season.
Keywords: waste management; municipal waste; waste collection; smart city